Współczesne wyzwania chrześcijaństwa - Doda-Wyszyńska, Agnieszka; Leciejewski, Sławomir (Człowiek i Społeczeństwo, 2022)
Is it possible to respond to contemporary challenges of Christianity from the meta-perspective of philosophy and cultural studies? We have divided the articles presented here into three groups: challenges faced by religion regarding science, challenges of secularisation, and challenges in the Church itself. The articles from the volume do not address these problems in totally different ways. The issues of consistency and rationality of religion become reinterpreted, for example when compared to results of empirical sciences, but also in a broadly understood public debate. We shall try to show a close relationship between the Christian religion and such phenomena as: science, media, churches, medicine, war, law, etc. Our point of departure is a search for the current function of Christianity, with the Catholic Church in the centre, but the questions transcend the present state of a particular religion.